Ultrasonography of the diaphragm in amyotrophic lateral sclerosis: Clinical significance in assessment of respiratory functions. Issue 2 (March 2013) - Hiwatani, Yasuhiro; Sakata, Mayumi; Miwa, Hideto
Abstract Our objective was to evaluate diaphragm thicknesses during respiration by ultrasonography, and compare with conventional measurements of respiratory functions in patients with amyotrophic lateral sclerosis (ALS). Thirty-six consecutive ALS patients and 19 age-matched healthy volunteers participated. Ultrasonography of the diaphragm in the zone of apposition was performed. Maximal diaphragm thickness during the maximal inspiratory effort (DTmax) and minimum diaphragm thickness at the end expiratory position (DTmin) were measured using ultrasonography. The thickening ratio (TR), defined as the ratio of DTmin to DTmax, was calculated. All patients underwent conventional pulmonary function testing. Arterial blood gas analysis was also performed. The diaphragm was clearly identifiable by ultrasonography. DTmax, DTmin and the TR were all significantly decreased in ALS patients with %VC (vital capacity) < 80, compared with those in either ALS patients with %VC ≥ 80 or healthy controls. DTmax, DTmin and the TR were all significantly correlated with %VC. In addition, significant inverse correlations were found between all three parameters and pCO2. The inter-observer reliability of measurements of diaphragm thickness was high. In conclusion, sonography of the diaphragm can provide additional or complementary information for assessing respiratory functions in patients with ALS.